Faktor-faktor yang Mempengaruhi Pemeriksaan VCT Pada Ibu Hamil di Puskesmas Puter - Sri Hennyati; Rosita .; Nurima Trianita (stikes dharma husada bandung, 2019)
VCT examination is a confidential dialogue between a person and a health worker that is a counselor who aims to help the person cope with stress and make personal decisions related to HIV / AIDS. This study was to determine the factors that affect the examination of VCT in pregnant women at Puter Health Center in 2017. Descriptive analytic research, population in this study were 140 respondents. Sampling technique is taken by using accidental sampling amounted to 35 respondents. Obtained that no correlation between education with VCT examination in Pregnant Women with p = 0,504> 0,05. Relationship between knowledge with VCT examination in Pregnant Women with p = 0.027 ≤ 0.05. family support and VCT examination in Pregnant Women with p = 0.001 ≤ 0.05, . the role of health professionals with VCT examination on Pregnant Women p = 0,015 ≤ 0,0, knowledge, husband support and the role of health professionals with VCT examination in Pregnant Women with ≤ 0.05. This research is suggested to pregnant women to take an active role in carrying out activities aimed at improving the health of pregnant women and their families, in this case conduct VCT examination as prevention effort of mother to baby.